Ameliorating quality and vase life of Solidago canadensis flowers via supplementation of eucalyptus, neem and rosemary as phyto-preserver oils - Iman Mohamed El-Sayed; Rasha Ahmed Mohamed El-Ziat; Hani Saber Saudy; Mohammed Hewidy (BMC Plant Biology)
Abstract Purpose The loss of flower quality after harvesting is a major concern in the floriculture industry. Because cut flower solutions are quickly contaminated with microbes, causing flower damage, they must be modified to enhance and extend the life of the vase. Methods Eco-friendly preservative solutions were examined to investigate the efficiency of natural essential oils of eucalyptus, neem and rosemary at concentrations of 200 and 400 mg L–1 each on the biological, physiological, and anatomical traits and vase life of solidago (Solidago canadensis) cut flower. Results Using different essential oils at both concentrations showed significant impact on cut flower longevity. The maximum vase life was obtained by solidago placed in a preservative solution containing 400 mg L–1 of neem essential oil, which enhanced water uptake and relative fresh weight and reduced both water loss and microbial count when compared to other treatments and control treatment. The chlorophyll, total phenol, flavonoid, and carotenoid content of the spikes increased in solidago cut-flower placed in a preservative solution containing neem essential oil 400 mg L−1. Results also showed decreased malondialdehyde (MDA), hydrogen peroxide (H2O2) levels and total antioxidant activity (DPPH radical-scavenging activity) with the application of all natural oils supply. Anatomically, cut flowers that treated with essential oils had considerably clearer vessels and significantly fewer bacteria than untreated cut flowers. Conclusion The higher concentration of different essential oils gave better results than the lower concentration. These results suggest that for the floriculture industry, natural phyto-oils provide a clear viable method to extend the vase life of solidago cut flowers. Thus, neem oil at a concentration of 400 mg L–1 added to a preservative solution is considered the most promising practice for prolonging the vase life and maintaining high quality of Solidago.